Pathway to academic well-being: The role of institutional social capital in the well-being of academics in five Central and Eastern European countries - Baltatescu, Sergiu; Hatos, Adrian; Artamonov, Volodymyr; Kovács, Klára (Central European Journal of Educational Research, 2026)
This study examined the relationship between institutional social capital and the emotional well-being of academics in Central and Eastern European higher education systems. Building on Pusztai’s conceptual framework, this study distinguishes between intragenerational social capital, referring to collegial cooperation and communicative exchange, and intergenerational social capital, referring to informal interaction with students beyond formal teaching. The analysis draws on survey data collected in 2023 from academics in five countries (Hungary, Romania, Slovakia, Serbia, and Ukraine) (N ≈ 800). Institutional social capital is operationalised through indicators capturing the frequency and diversity of interactions, while emotional well-being is measured using Warr’s Affective Well-being Scale. The results show that intragenerational social capital is a significant positive predictor of well-being, whereas intergenerational social capital has no independent effect. The findings suggest that collegial relational embeddedness constitutes a relevant, albeit limited, resource for emotional well-being in academic work.